Efficacy and safety of intense pulse light in idiopathic hirsutism - Kumari, Rakhi; Shaikh, Irfan Ahmed; Abbasi, Romana; Tarbani, Kailash; Kumari, Meena (Journal of Pakistan Association of Dermatologists, 2019)
Background Unwanted facial hair can cause severe cosmetic, social and psychological problems. Light assisted hair removal using lasers and intense pulsed light (IPL) sources because of their long term results and safety, have emerged as a promising method in hair removal. Objective To determine the efficacy and safety of IPL in the treatment of idiopathic facial hirsutism. Materials and Methods 90 cases of idiopathic hirsutism were enrolled. All were Asian females with Fitzpatrick skin type III, IV; age range was 18 to 45 years, treated at 4-6 week interval. The response of treatment was assessed after every sitting (session) by grading visual scale analogue i.e. Excellent (>80% reduction in hair density), Good (>50% reduction in hair density), Fair (>30% reduction in hair density). Results Total 90 cases participated; participants were divided into three groups, A, B and C on the basis of completion of sessions, 10, 6 and 4 sessions respectively. 23 cases fall in group A, 31 and 36 in group B and C respectively. Mean age was 26.34±6.39. Excellent response seen in 69.5% cases in Group A, 16.1% cases in group B, while 16.6% cases in group C, with minimum complications, which was statistically significant p=0.000. There was no significant difference between age groups in response to IPL (p=0.66), also not statistically difference between marital status and response of IPL (p=0.99). Conclusion Intense pulsed light is a good treatment option in idiopathic hirsutism, without any major side effects.